PENGARUH PERTUMBUHAN EKONOMI DAN PAD TERHADAP KUALITAS PEMBANGUNAN SUMBER DAYA MANUSIA DAN TINGKAT KEMISKINAN - Khalid Billady, Teguh; Marhaeni, A. A. I. N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.08.TAHUN 2019, 2019)
The aim in this study is to determine the effect of economic growth and local regional revenue on the quality of human resource development and poverty levels, and to determine the effect of economic growth and local regional revenue on poverty levels through the quality of human resource development in districts / cities Bali province. Data collection methods used in this study are observation methods and use secondary data. The analysis technique used is path analysis. The results showed that economic growth and local regional revenue had a positive and significant effect on the quality of human resources and economic growth and local regional negative and significant affected the level of poverty and economic growth and local regional revenue had a negative and significant influence on the level poverty through the quality of human resource development in the districts / cities of the Province of Bali.